Harmonizing routinely collected health information for strengthening quality management in health systems: requirements and practice. (October 2016) - Prodinger, Birgit; Tennant, Alan; Stucki, Gerold; Cieza, Alarcos; Üstün, Tevfik Bedirhan
Objective: Our aim was to specify the requirements of an architecture to serve as the foundation for standardized reporting of health information and to provide an exemplary application of this architecture. Methods: The World Health Organization's International Classification of Functioning, Disability and Health (ICF) served as the conceptual framework. Methods to establish content comparability were the ICF Linking Rules. The Rasch measurement model, as a special case of additive conjoint measurement, which satisfies the required criteria for fundamental measurement, allowed for the development of a common metric foundation for measurement unit conversion. Secondary analysis of data from the North Yorkshire Survey was used to illustrate these methods. Patients completed three instruments and the items were linked to the ICF. The Rasch measurement model was applied, first to each scale, and then to items across scales which were linked to a common domain. Results: Based on the linking of items to the ICF, the majority of items were grouped into two domains, Mobility and Self-care. Analysis of the individual scales and of items linked to a common domain across scales satisfied the requirements of the Rasch measurement model. The measurement unit conversion between items from the three instruments linked to the Mobility and Self-care domains, respectively, was demonstrated. Conclusions: The realization of an ICF-based architecture for information on patients' functioning enables harmonization of health information while allowing clinicians and researchers to continue using their existing instruments. This architecture will facilitate access to comprehensive and consistently reported health information to serve as the foundation for informed decision-making.